Reported associations between kratom and seizures: a systematic review - Turla, Toby; Abele, Grayson; Hua, My; Paustenbach, Dennis (Frontiers in Pharmacology, 2025)
Statement of purpose, innovation or hypothesisKratom, derived from the leaves of the plant Mitragyna speciosa, is an herbal supplement that has been used medically and recreationally for centuries, but has recently gained popularity in the United States for its analgesic and euphoric effects. The United States Food and Drug Administration (US FDA) has issued warnings against the use kratom due to potential health effects, including seizures. Seizures are one of the most commonly reported side effects associated with kratom use. The purpose of this paper is to determine whether there is a causal relationship between kratom use and seizures.Description of methods and materialsA systematic literature search was conducted to identify reviewed articles that contained information or data on kratom users experiencing seizures. Additionally, we mined adverse event data submitted to the Centers for Food Safety and Applied Nutrition’s Adverse Event Reporting System (CAERS) database and the US FDA Adverse Event Reporting System (FAERS). These databases were selected to examine consumer-reported and healthcare-reported adverse event, providing a comprehensive list of seizure-related incidents potentially associated with kratom use.Data and resultsOur search yielded a total of 42 articles, but only 11 met the selection criteria for inclusion. The 11 peer-reviewed articles included for analysis consisted of case reports (n = 6), case series (n = 2), retrospective observational (n = 2), and a paper discussing a summary of adverse events reported to the FAERS database. Across the 11 publications used in our analysis, we noted a total of 20 patients who reportedly experienced seizures after using kratom. However, only one patient was quantitatively positive for Mitragynine in their urine sample, so there was minimal proof of kratom use. There was no indication that the other 19 patients had their urine subjected to mitragynine screening which would have confirmed their use of kratom and internal metabolism after intake. Furthermore, the FAERS dashboard, only 22 of 481 kratom-related reports involved seizure (4.5%); the CAERS database had 18 reported seizures amongst 221,178 kratom-related incidents. Information regarding the quantity of kratom consumption or confirmed use of kratom was not available in any of the datasets reviewed.Interpretation, conclusion or significanceCurrently, the available literature primarily consists of a limited number of studies, including case reports and case series, which document self-reported kratom use and provide minimal quantitative toxicological data on mitragynine. Based on our narrative review, we conclude that there is insufficient evidence to suggest that kratom causes seizures, primarily due to the absence of a quantitative dose-response in toxicology reports, a incomplete medical records and because seizures occur relatively frequently in the general population.